Analysis of Sustainable Energy Metrics in Douala’s Road Transportation Sector, Cameroon - Bissai, Fontaine Dubois; Mbanga, Bienvenu Gaël Fouda Fouda; Adiang Mezoue, Cyrille; Nguiya, Severin (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2023)
In this study, Douala, Cameroon was used as a case study to analyze the characteristics of sustainable energy for road transport from 2010 to 2019. Douala, being the national capital and entry point to Central Africa, served as a major hub for the movement of people and goods. However, the road transport sector was plagued by a number of problems, including traffic congestion, the use of fossil fuels, air pollution, and global warming associated with road traffic. The objective of this work was to evaluate a set of indicators that would allow monitoring the evolution of trends in the interactions between the energy component and sustainable development. The DPSIR (Driving Force, Pressure, State, Impact, and Response) model was used to select a set of indicators. According to the results, the energy intensity of the fuel used for transport decreased from 9.93 to 15.9 toe/M€. This increase in energy intensity reflected the energy-intensive nature of the road industry. Additionally, from 2010 to 2019, the energy efficiency of road transport vehicles in the city of Douala fluctuated between 20 and 22%. This indicates a significant potential for improving energy efficiency. Therefore, decision-makers need to implement sustainable transport planning to address these issues.